Teori Kecerdasan dan Teori Motivasi Belajar - Dini, Wahyu; Dikdik. F. Dermawan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study use a qualitative approach with a literature review to collect and analyze written sources. The results indicate that intelligence is defined as the ability to find solutions to problems quickly and accurately. Four main theories discussed regarding intelligence are Multiple Intelligences, Triarchic Intelligence, General Factor Intelligence, and Emotional Intelligence, all of which show the complexity and multidimensionality of human intelligence. Meanwhile, learning motivation is defined as a vital psychological drive to improve achievement and optimize students' potential. This article also recognizes various forms of motivation that can be applied in learning, including giving numbers, prizes, competitions, ego involvement, exams, knowing learning outcomes, praise, punishment, desire, and interest.